View it as Investment - Sudhkar Rao, Y. (Indian Forester, 1968)
The need for cultivating the discipline of economics by foresters is emphasised. The requirement of the various Industries projected to 1975 is briefly stated. Economics of raising plantations of Bamboo, Eucalyptus and Teak are dealt in a comparative manner. The need for selecting the best sites available even for species which can thrive on poorer soils is emphasised. The need and method of planning of plantation schemes is touched upon.